(untitled) (Bangladesh Rice Journal, 2021)
Weed causes huge reduction in crops yield, increases cost of cultivation, reduces input efficiency, interferes with agricultural operations, impairs quality, act as alternate hosts for several insect and diseases .Yield loss due to improper weeding at farmer’s field ranged from 4 to 22% depending on different rice ecosystem in Bangladesh. But at present considering all the cultivable land across the country and other issues; yield loss due to weeds considered about 2% in a consultation meeting.The present weed control practices in Bangladesh are characterized by intensive use of manual labour, use of herbicide and certain mechanical weeding. Manual weeding, besides laborious is inefficient as it is not done in time in most of the cases and always not practical because of various adverse conditions. Cost effective and integrated weed management system should be adopted to increase economic gain and sustainable rice production. Adopting timely and effectively appropriate weed management techniques we can reduce a significant amount of yield loss and about 0.43 million ton (MT) additional yield could be increased by 2030. To achieve the target weed management should be done from the very beginning of rice production and up to 30-35 DAP (days after planting) for Aus season, 35-40 DAT (days after transplanting) for T. Aman season and 40-45 DAT for Boro season which indicates critical period of weed infestation in Aus, T. Aman and Boro season. The main approach is that rice field have to keep free from weed up to that days by 2/3 hand weeding (HW) or application of herbicide fb (Followed by) 1HW or applying weeder fb 1HW which is called integrated weed management. Herbicide should be applied at proper time and dose which reduce 61% weeding cost. Mechanical weeding (MW) reduces 50% weeding cost that keeps environment friendly. Future weed science research specially herbicide efficacy with correct time and dose, new molecule herbicide with low environmental effect, herbicide residues in soil plant system, bioherbicide, allelopathic variety, weed competetive variety, mechanical weeder with related technological developments need a multidimensional approach for ecologically sustainable integrated weed management. Such a system will work toward a socially permissible, environmentally sound, economically feasible, productive and sustainable agricultural system. Bangladesh Rice J. 24 (2): 133-159, 2021